Modernization and Commercialization of Armenian Agriculture : Priorities for Sector Reform and Investment - World Bank Group (World Bank, Washington, DC, 2017)
The study focuses on themes and areas that have been identified as highly relevant for the modernization and commercialization of the agriculture sector. The study originally aimed to review: agricultural marketing, processing and exports; food safety; agricultural “cooperation,” including farmers’ groups; agricultural extension and agricultural insurance. This coverage was subsequently modified to: (i) avoid repetition of existing work; (ii) draw more extensively on WBG experience in other countries; (iii) address relevant long-term issues more directly; and (iv) to inform discussion of relevant issues on which little information was available. The proposed review of marketing, processing and exports, an area that has already been well studied – was thus replaced with a review of global experience in developing successful export-led agricultural industries. Similarly, the study of agricultural ‘cooperation,’ an area also widely studied, was replaced with an analysis of agricultural land markets. Both “cooperation” and land markets are highly pertinent to the need to increase farm size to improve competitiveness. Land markets offer a more structural, long-term response to this problem, however, a response that so far has received little attention. Finally, an analysis of public expenditure on agriculture was added to provide insight into public expenditure on long-term versus short-term sector objectives. The review outlines the elements of a long-term framework based on building a cluster-based, institutional framework for horticultural exports, and suggests the need to prioritize associated development of agricultural extension, food safety, agricultural land markets and agricultural risk management. Horticulture is viewed as a vector for modernization and commercialization, due to its demonstrated potential for exports. The proposed framework would drive growth and change throughout the sector, however, due to the sector-wide impact of support for extension, food safety, land markets and risk management.